2016
DOI: 10.2166/wst.2016.149
|View full text |Cite
|
Sign up to set email alerts
|

Sewage sludge pretreatment by microwave irradiation combined with activated carbon fibre at alkaline pH for anaerobic digestion

Abstract: This research focuses on the effects of microwave-assisted activated carbon fibre (ACF) (MW-ACF) treatment on sewage sludge at alkaline pH. The disintegration and biodegradability of sewage sludge were studied. It was found that the MW-ACF process at alkaline pH provided a rapid and efficient process to disrupt the microbial cells in the sludge. The results suggested that when irradiated at 800 W MW for 110 s with a dose of 1.0 g ACF/g solid concentration (SS) at pH 10.5, the MW-ACF pretreatment achieved 55% S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The VS reduction of MI pre-treated sludge was observed to be higher than that of conventional heating and was attained in a lesser amount of time. Sun et al, (2016) found that after 20 days of AD, the MI-Alkaline Carbon Fibre process at an alkaline pH attained an increase in biogas production of 63.7% in comparison to the untreated experiment.…”
Section: Microwave Irradiationmentioning
confidence: 91%
“…The VS reduction of MI pre-treated sludge was observed to be higher than that of conventional heating and was attained in a lesser amount of time. Sun et al, (2016) found that after 20 days of AD, the MI-Alkaline Carbon Fibre process at an alkaline pH attained an increase in biogas production of 63.7% in comparison to the untreated experiment.…”
Section: Microwave Irradiationmentioning
confidence: 91%
“…Then, Cr(VI) remaining concentrations were determined by a HASH water quality analyser (DR2800, U.S.A). The maximum amount adsorbed (q m ) was calculated by Equation (1) [22]:q m = [(C 0 − C r )/V]/m where C 0 and C r are initial and final concentrations of Cr(VI) (mg·L −1 ), respectively, V is the solution volume(L) and m is the mass of N-SAC(g).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, digested sludge (or digestate) becomes easier to dewater, transport, and dispose. However, even under typical retention times of 20–30 days, decomposition of sludge in AD is incomplete, leaving 35%–45% of organic matter undigested. This inefficiency is attributed to the rate-limiting hydrolysis step, , which precedes acidogenesis, acetogenesis, and methanogenesis. , …”
Section: Overview Of Spion-augmented Microwave-based Sludge Prehydrol...mentioning
confidence: 99%